Psychological Diagnosis of Master Students’ Personal, Professional Development in the Context of Modern Education - Laura, Shalabayeva; Saya, Baisultanova; Saule, Alimbayeva; Magripa, Ibrayeva; Ulzharkyn, Abdigapbarova (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The article’s psychological diagnosis of master students’ personal, professional development is considered a process of professional socialization and professional development. Undergraduates, as future researchers, teachers of educational activity are required to have certain professional qualities. The research aims to determine the dynamics of professional development of graduates in science and pedagogical process. For this purpose, the method Cattell (16PF, scale C), the diagnostic questionnaire of personality status and traits (FPI), a questionnaire of Otto Lipmann (1 variant), the questionnaire of "The level of subjective control," by J. Rotter have been used. While studying, it was underlined that master students possess: increased externalities trends in personal and industrial relations (i.e., the main areas for the teacher relationship), strengthening conservative tendencies in behavior, as opposed to radicalism and other professional qualities for teaching and research activities. Successful undergraduate is characterized by a greater tendency to depression, compared to less successful, he is more sensitive, competent, internality, and responsible for achieving, and creative. It was noted that the factor structure of variant individuality-personal features of undergraduates includes the factors of "professional competence," "professional motivation," and "professional internality."